Chemical Tools for Targeted Amplification of Reactive Oxygen Species in Neutrophils - Reshetnikov, Viktor; Hahn, Jonas; Maueröder, Christian; Czegley, Christine; Munoz, Luis Enrique; Herrmann, Martin; Hoffmann, Markus H.; Mokhir, Andriy (Frontiers in Immunology, 2018)
A number of chemical compounds are known, which amplify the availability of reactive oxygen species (ROS) in neutrophils both in vitro and in vivo. They can be roughly classified into NADPH oxidase 2 (NOX2)-dependent and NOX2-independent reagents. NOX2 activation is triggered by protein kinase C agonists (e.g. phorbol esters, transition metal ions), redox mediators (e.g. paraquat) or formyl peptide receptor agonists (e.g. aromatic hydrazine derivatives). NOX2-independent mechanisms are realized by reagents affecting glutathione homeostasis (e.g. L-buthionine sulfoximine), modulators of the mitochondrial respiratory chain (e.g. ionophores, inositol mimics and agonists of peroxisome proliferator-activated receptor γ) and chemical ROS amplifiers (e.g. aminoferrocene-based prodrugs). Since a number of inflammatory and autoimmune diseases, as well as cancer and bacterial infections, are triggered or enhanced by aberrant ROS production in neutrophils, it is tempting to use ROS amplifiers as drugs for the treatment of these diseases. However, since the known reagents are not cell specific, their application for treatment likely causes systemic enhancement of oxidative stress, leading to severe side effects. Cell-targeted ROS enhancement can be achieved either by using conjugates of ROS amplifiers with ligands binding to receptors expressed on neutrophils (e.g. the GPI-anchored myeloid differentiation marker Ly6G or formyl peptide receptor FPR) or by designing reagents activated by neutrophil function (e.g. phagocytic activity or enzymatic activity of neutrophil elastase). Since binding of an artificial ligand to a receptor may trigger or inhibit priming of neutrophils the latter approach has a smaller potential for severe side effects and is probably better suitable for therapy. Here we review current approaches for the use of ROS amplifiers and discuss their applicability for treatment. As an example we suggest a possible design of neutrophil-specific ROS amplifiers, which are based on neutrophil elastase-activated aminoferrocene-based prodrugs.